Epidemiology and Risk Mapping of hard ticks (Ixodidae) infecting Small Ruminants in Khyber Pakhtunkhwa Province, Pakistan - Iqbal, Z; Afshan, K; Kayani, AR; Ahmad, H; Irfan, M; Qayyum, M (Journal of the Hellenic Veterinary Medical Society, 2023)
Ticks and tick-borne diseases (TBDs) cause a negative impact on animal health and production globally. Because of the transhumant production system of sheep and goats in Khyber Pakhtunkhwa (KP), Pakistan, registration and tracking system of animals is not possible, which is a prerequisite for the development of early warning systems for any outbreak of TBDs. Therefore, the present study was aimed to investigate the district-wise surveillance and risk mapping to find the epidemiological profile of tick infestation in small ruminants from KP, Pakistan. Ticks (n=6257) were collected from the six selected districts from May 2017- April 2018. A total of 1500 animals (goats=618 and sheep=881) were screened for the presence of ticks on different host predilection sites. A questionnaire depicting epidemiological information was filled, and a geographic information system (GIS) was used to map the risk areas. The study identified six tick species namely, Rhiphicephalus (R.) microplus, Hyalomma (H.) trancatum, H. anatolicum, H. aegyptium, H. asiaticum, and Haemaphysalis bispinosa. The tick prevalence in study districts was 16% in Peshawar, 15.67% Mardan, 12.8% Bannu, 18% Mansehra, 15.67% Mingora, and 21.87% in Dera Ismail Khan. R. microplus was only prevalent in Peshawar (36.18 %) and in Dera Ismail Khan (63.81 %) districts, while Haemaphysalis bispinosa and H. aegyptium were only recorded in Mardan. The intensity of Hyalomma spp. was recorded at 62.92 % followed by Rhipicephalus spp., 36.55%, and Haemaphysalis spp., 1.15%. Hyalomma spp. showed the highest prevalence on all host predilection sites viz: ears (62.2 %), groin areas (60.8%), under the tail (61.9 %), testicular areas (63.2 %), breast (64.5 %), and in hooves (64.7%) as compared to Rhipicephalus and Haemaphysalis species. Similarly, in sheep and goats, the adult ticks were more prevalent in age group 1-2 years (83.28% and 68.98%) followed by < 1 year of age group (82% and 68.89%), respectively. The results revealed high female (61.9%) tick infestation as compared to male ticks (38.1%), whereas the highest female to male tick ratio was 1.77:1 in Haemaphysalis species. The GIS map demonstrated that the degree of tick infestation varied within districts and villages. In conclusion, results recorded that economically vital ticks are extensively distributed all over the KP province and cost-effective control studies are needed to minimize the spread of tick-borne diseases.